Intermolecular interaction effects on the ultrafast depolarization of the optical emission from conjugated polymers. - Chang, M; Frampton, M; Anderson, H; Herz, L (2007)
We have investigated the effect of interchain interactions on the ultrafast depolarization of the photoluminescence from solid films of a conjugated polymer. Accurate control was exercised over the interchain separation by threading of the conjugated chains with insulating macrocycles or complexation with an inert host polymer. Our measurements indicate that excitation into the higher electronic states of a chain aggregate is followed by a fast (<100 fs) relaxation into lower excited states with an associated rotation of the transition dipole moment. These findings emphasize the need for consideration of initial excitonic delocalization across more than one polymeric chain.